Requirements engineering for User-Centered school food ordering system - Diyana Binti Halim Khoo; Afdallyna Fathiyah Harun; Saiful Izwan Suliman (Institute of Advanced Engineering and Science, 2020)
Understanding user requirement for a technology design is central to user experience. A user-centered technology design should consider user needs and constraints as well as abide to the principles of HCI design heuristics. This paper describes the requirements gathering for Kantin Online System, a school food ordering system where we considered the needs and constraints of different stakeholders involved and elicit a compromise where the needs of all parties can be met. We then applied usability heuristics into the system design to facilitate perceived ease of use and perceived usefulness. We conclude this paper with experts’ evaluations towards the heuristic elements of the system design concept and possible future work.